Synthesis of compound libraries for the study of glucose uptake and splicing inhibition - Ceballos Cerrajería, Javier de (Technische Universität Dortmund, 2017)
Despite having the same "purpose", the uncontrollable cellular growth to the detriment of the organism, cancer presents itself in humans in great variety of forms. This variety makes developing effective treatments a highly challenging task. Nevertheless, cancer has a handful of hallmarks that are present almost ubiquitously in all types of tumours. Among them is the upregulated glucose uptake, known as the Warburg effect. However, there has yet to be a drug or treatment that makes use of this aberrant cancer metabolism. This is due to the lack of potent glucose uptake inhibitors. The identification of small molecules that efficiently target the glucose uptake is hence of high value. Through an in-house established glucose uptake assay, new scaffolds were identified as glucose uptake inhibitors, such as the Glupins. This novel identified scaffold presented a natural product-like structure and a high potency. In the present work, a synthetic route towards the Glupin core was established. The structure-activity relationships of the Glupin class was extensively studied by the synthesis of a library of analogues. The analogue, (+)-Glupin-1, was discovered as one of the most potent glucose uptake and was therefore selected for further biological studies.The splicing process, the process by which premature messenger RNA is transformed into a mature form ready to be translated, is performed by a highly complex machinery, the spliceosome. The splicing process occurs in a series of steps, each of them catalysed by a different spliceosome complex constituted by many proteins and ribozymes. Decades of research on the spliceosome complex have provided an understanding of the process but much remains to be discovered. The in-house identification of a novel splicing inhibitor, cp028, enabled the isolation of a previously unknown spliceosome stage. In this work, the cp028 compound was studied with the synthesis of a library of analogues around its core. The library of analogues was assayed as splicing inhibitors yielding a SAR analysis of this novel class. Furthermore, efforts towards the identification of the cp028 target were made. Cp028 joins a short list of powerful splicing inhibitor that have allowed for a deeper study of the splicing process and opens the door for the identification of novel key protein players of this highly complex process.
Keywords: Glucose uptake; Aerobic glycolysis; Splicing inhibition; Structure-activity relationship; 570; 540; Glycolyse